Isolasi dan Karakterisasi Bakteri Asam Laktat pada Food Replacement ‘X’ dan Fermentasi Akar Teratai - Br Pinem, Elys Dayanty; Bangar, Roy Indrianto; Lubis, Asyrun Alkhairi (Lembaga Pengembangan Kinerja Dosen, 2026)
Functional foods provide additional health benefits beyond their nutritional value. One approach in the development of functional foods is through fermentation involving lactic acid bacteria (LAB). This study aims to isolate and characterize lactic acid bacteria produced from the fermentation of lotus root and food replacement X as alternative food ingredients. The study was conducted experimentally through a five-day fermentation process at 37°C. The results show that LAB was successfully isolated from the fermentation of lotus root with a colony count of 1.88 × 10⁵ CFU/mL at a 10⁻² dilution, while no LAB growth was found in food replacement X. Four pure isolates were obtained with colony characteristics of round shape, milky white color, non-motile, and catalase-negative. Two isolates were Gram-positive, while the other two were Gram-negative. All isolates showed the ability to survive in acidic pH conditions (pH 3), with isolate EDP 1 having the highest resistance. The results indicate that lotus root fermentation has the potential to be a source of LAB for functional food applications.